SEO (Search Engine Optimization) Finding Growth Opportunities in Organic Traffic on the KAIA Media.id Website - Yoga Pramana; Halim Maulana (Ilmu Bersama Center, 2026)
The rapid growth in digital marketing highlights the importance of Search Engine Optimization (SEO) in enhancing website visibility and attracting organic traffic. This research focuses on SEO optimization for Kaia Media.id by developing a dedicated Keyword Tool Suggestion application. The primary goal is to identify opportunities to increase organic traffic to the Kaia Media.id website by efficiently targeting relevant keywords. The developed tool helps discover high-potential keywords that align with the interests and search behavior of the target audience. The Keyword Tool Suggestion application provides an easy-to-use interface to generate effective keyword suggestions based on current trends and search engine algorithms. By integrating this tool into Kaia Media.id's SEO strategy, the website can improve its search engine ranking, attract more visitors, and ultimately enhance its online presence. The application is tested to ensure that it provides accurate and actionable keyword suggestions, facilitating more effective content creation and marketingstrategies. By leveraging the Keyword Tool Suggestion application, Kaia Media.id aims to position itself as a leading digital marketing agency, offering high-quality SEO and online marketing solutions to its clients. The findings of this research affirm the value of targeted keyword optimization in achieving sustainable growth in organic traffic.